(untitled) (PANGEEA, 2025)
The current problems signaled by the academical world with reference to the Roma are, first of all, connected to resources (both material and non-material). The causes and effects of the phenomenon are multiple and they are linked to some key aspects for the Roma in Romania, such as life standard, employment, education, and health. Connected to the above mentioned issues, there is also the problem of dwelling (houses and areas where Roma communities are set). There is a strong connection between the economical power and the residence type which has a multifold effect on the individual and community life. Some aspects regarding living on the periphery of the localities will be tackled in this research.